Comprehensive assessment of the physical and health features of the threatened Araguaian River dolphin Inia araguaiaensis. - Daniela M D de Mello; Waleska Gravena; Aricia Duarte-Benvenuto; Alan S Lima; Fernando R Gomes; Vera M F da Silva (PLoS ONE)
The Araguaia River dolphin is endemic to the Tocantins-Araguaia River Basin and is under severe anthropogenic threats. Given the species' vulnerability and historical neglect, preliminary data on its health and physical parameters are presented, along with an evaluation of potential differences between individuals from areas with varying human activity. A comparison of these data with its closely related species, the Amazon River dolphin I. geoffrensis, was also aimed. Twenty-four dolphins were captured and released in Cantão State Park (protected area, n = 10), Tocantins state; and Luiz Alves (exposed to fishing activities, n = 14), Goiás state. Preliminary data indicates no significant differences in the body morphology and physical parameters between individuals from the two areas. Araguaia River dolphins tended to show larger grey areas in their bodies than their counterparts, Amazon river dolphins. Cardiac rate, respiratory frequency, and oral temperature did not vary between individuals from different areas, sex, or age classes. Hematological and serum chemistry variables differences were observed among age classes, mainly related to body and immune system development. Dolphins from Cantão had higher AST and urea/creatinine and lower GGT, total bilirubin, and creatinine than dolphins from Luiz Alves. Such variations may reflect different prey types, intensities of muscle extenuation during capture, or subclinical diseases. Most hematological parameters for the Araguaia River dolphin were outside the reference intervals described for the Amazon river dolphin but inside its minimum and maximum ranges. Conversely, the serum chemistry values from both species overlap with the reference values. The highest serum testosterone was detected in adult males and the highest serum progesterone and estradiol in adult females. Correlations between reproductive hormones and body measurements demonstrated preliminary hormonal variation according to the body's development as the individuals reach sexual maturity. Understanding the current physical and health status of individuals from areas with different human activity intensities is crucial to drive management efforts toward species conservation.